2-1/2x=11x-6

Simple and best practice solution for 2-1/2x=11x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-1/2x=11x-6 equation:


x in (-oo:+oo)

2-((1/2)*x) = 11*x-6 // - 11*x-6

2-((1/2)*x)-(11*x)+6 = 0

(-1/2)*x-11*x+2+6 = 0

8-23/2*x = 0 // - 8

-23/2*x = -8 // : -23/2

x = -8/(-23/2)

x = 16/23

x = 16/23

See similar equations:

| 2x-3(x+2)-9= | | 9p^2-18p-88=0 | | (-4)-(-6)=3 | | -2(2r+5)=-6(r+2) | | 26-(3x+12)=11-4(x+1) | | 32/4=8/3 | | .25(2.5x+1.5(x-4))=-x | | 2/3+3m/5=21/15 | | 3x-x+10=4x+12 | | 12x+10*2*5=45 | | 2(3c-4)=8c+1 | | g(x)=x-60 | | 16h^2+0h-25=0 | | 36x+63=9(4x+7) | | X+6+7x=46 | | 4-5(x+3)=4x+7 | | 2/9+5/36 | | m+8m+9m-7= | | 11x-2+75=7 | | 2x+56=3 | | 6+2+(-4)= | | x-15x=6x-15-x | | 2a-5(8)=10 | | x+x+1/2+1/2 | | 67=7x+3x+7 | | 3x+17x-6=4(5x+2) | | (2-2t)7-10+7t= | | 3m-2-1m=-2+m-5 | | x+5(x+2)=53 | | 4(b-4)+9=2(4b-6) | | 63-6.1x=2.9x | | 3x+5=2x+-7 |

Equations solver categories